2007
DOI: 10.1016/j.ejcts.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous veno-venous hemodiafiltration in children after cardiac surgery

Abstract: We conclude that CVVHDF may be an alternative method of renal support for critically ill children after cardiac surgery in experienced centers, but a significant number of specific complications should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
6
29
2
4
Order By: Relevance
“…Carrying out constant HF/HD in infants makes it possible to achieve the necessary fluid balance, and decreases in CVP and Pla are accompanied by MAP and LVEF increases, which allow inotropic support reduction in some cases. [13] We are in strong agreement with researchers who believe that hemodynamic and gas exchange improvements are associated with the optimization of circulating blood volume and plasma colloid osmotic pressure. [5] We also think that blood purification's positive effects are implemented by filtration of interstitial fluid excess and reduction of myocardial and pulmonary edema.…”
Section: Blood Purification For Acute Kidney Injuryin Patients With Msupporting
confidence: 77%
“…Carrying out constant HF/HD in infants makes it possible to achieve the necessary fluid balance, and decreases in CVP and Pla are accompanied by MAP and LVEF increases, which allow inotropic support reduction in some cases. [13] We are in strong agreement with researchers who believe that hemodynamic and gas exchange improvements are associated with the optimization of circulating blood volume and plasma colloid osmotic pressure. [5] We also think that blood purification's positive effects are implemented by filtration of interstitial fluid excess and reduction of myocardial and pulmonary edema.…”
Section: Blood Purification For Acute Kidney Injuryin Patients With Msupporting
confidence: 77%
“…It has been reported that 1% -17% of patients with AKI require RRT (3). In this setting, PD or continuous venovenous hemodiafiltration can be offered to (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, PD or continuous venovenous hemodiafiltration can be offered to (3,4). In smaller children, PD may have some advantages because it obviates the need for a vascular catheter and is well tolerated in patients with hemodynamic instability (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove the excessive volume and inflammatory mediators, RRT might be necessary to improve prognosis. [28][29][30][31][32][33] It is known that RRT is beneficial to patients with sepsis-related MODS because of its capacity to remove cytokines; early use of RRT might improve prognosis in patients with SIRS and sepsis. [34][35][36][37] It was demonstrated that early initiation of CRRT could improve outcome in AKI patients who underwent cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%